Computational and theoretical studies of nodal joints in monolithic buildings - T. A. Belash; A. V. Kuznetsov (Vestnik MGSU)
Introduction. The civil engineering sector in large regions of Russia is mainly represented by monolithic housing construction. A typology of constructive solutions for interfaces between floor slabs and a wall is given. The analysis of such constructive solutions during operation is carried out. Defects and damages formed in the cantilever part of the perforated floor slab were determined. A numerical study of the stress-strain state of nodal joints was carried out, taking into account natural and climatic influences. An assessment of the performance of such buildings is given. Improved and new types of junctions of floor slabs with an outer wall are proposed.Materials and methods. The section of the floor slab with perforation for thermal liners is considered. The numerical experiment carried out in the ANSYS software package included the construction of a three-dimensional model of a perforated slab fragment in the Design Modeler module. A finite element mesh of Solid 45 type, represented as three-dimensional 8-node volume elements, was generated using the Mesh module. The Elemental Difference solver was used to improve the accuracy of calculations. Temperature effects were taken into account as boundary conditions, force effects from the weight of enclosing wall structures on the cantilever part of the slab were not taken into account.Results. A numerical study of the interface nodes of the floor slab with the wall was carried out. It was determined that in the cold period of the year, in heated buildings of the type under consideration, the destruction of the protective layer of concrete occurs in the zone of alternating temperature effects, which leads to the fact that in the perforated floor slab, the nature of the multi-cycle temperature effects forms the appearance of cracks and destruction of concrete on the side surfaces of the keys. The results of numerical simulation showed that under the action of negative outdoor temperatures, the greatest stresses occur at the junctions of perforations with keys and exceed the standard values of the calculated stress by 1.4 times. For example, for the ratio a/b equal to 100/100, the values of normal stresses ϭz amounted to 1.16 MPa, taking into account temperature and climatic influences in the cold season. New types of design solutions are proposed for the junctions of the floor slab with the wall, which allow to reduce the values of normal stresses to a level that does not exceed the standard values of the design compression resistance established by CP 63.13330.2018.Conclusions. Based on the performed studies, it was found that the most vulnerable point of the floor slabs with perforation are key connections, which are influenced by cyclic temperatures. Based on the results of multifactor analysis of the stress-strain state of the floor slab with perforation for thermal inserts, taking into account the geometric parameters of perforation and temperature and climatic influences, the causes of vulnerabilities were established, the appearance of which is associated with high values of normal and tangential stresses exceeding the maximum permissible at negative outdoor temperatures, leading to the initial localization of destruction. The improvement of the operational qualities of monolithic buildings is ensured by the use of improved structures. The proposed design solutions make it possible to solve issues related to durability and safety during the operation of civil facilities.